Glutamine-αKG axis affects dentin regeneration and regulates osteo/odontogenic differentiation of mesenchymal adult stem cells via IGF2 m6A modification - Qinglu Tian; Shiqi Gao; Siying Li; Mian Wan; Xin Zhou; Wei Du; Xuedong Zhou; Liwei Zheng; Yachuan Zhou (Stem Cell Research & Therapy, 2024)
Abstract Background Multi-lineage differentiation of mesenchymal adult stem cells (m-ASCs) is crucial for tissue regeneration and accompanied with metabolism reprogramming, among which dental-pulp-derived m-ASCs has obvious advantage of easy accessibility. Stem cell fate determination and differentiation are closely related to metabolism status in cell microenvironment, which could actively interact with epigenetic modification. In recent years, glutamine-α-ketoglutarate (αKG) axis was proved to be related to aging, tumorigenesis, osteogenesis etc., while its role in m-ASCs still lack adequate research evidence. Methods We employed metabolomic analysis to explore the change pattern of metabolites during dental-pulp-derived m-ASCs differentiation. A murine incisor clipping model was established to investigate the influence of αKG on dental tissue repairment. shRNA technique was used to knockdown the expression of related key enzyme-dehydrogenase 1(GLUD1). RNA-seq, m6A evaluation and MeRIP-qPCR were used to dig into the underlying epigenetic mechanism. Results Here we found that the glutamine-αKG axis displayed an increased tendency along with the osteo/odontogenic differentiation of dental-pulp-derived m-ASCs, same as expression pattern of GLUD1. Further, the key metabolite αKG was found able to accelerate the repairment of clipped mice incisor and promote dentin formation. Exogenous DM-αKG was proved able to promote osteo/odontogenic differentiation of dental-pulp-derived m-ASCs, while the inhibition of glutamine-derived αKG level via GLUD1 knockdown had the opposite effect. Under the circumstance of GLUD1 knockdown, extracellular matrix (ECM) function and PI3k-Akt signaling pathway was screened out to be widely involved in the process with insulin-like growth factor 2 (IGF2) participation via RNA-seq. Inhibition of glutamine-αKG axis may affect IGF2 translation efficiency via m6A methylation and can be significantly rescued by αKG supplementation. Conclusion Our findings indicate that glutamine-αKG axis may epigenetically promote osteo/odontogenic differentiation of dental-pulp-derived m-ASCs and dentin regeneration, which provide a new research vision of potential dental tissue repairment therapy method or metabolite-based drug research.